From Dusting to ‘Deening’ - Quraisha Dawood (The Thinker)
Domestic workers in South Africa continue to tread the blurry line between formal and informal work. Despite attempts to regulate remuneration and organise workers, around 863,000 domestic workers earn their livelihoods within homes across the country. Comprised predominantly of black, semi-skilled women, authors have argued that this often-invisible workforce is vulnerable to exploitation, violence, and an insurmountable workload. Literature, however, hardly acknowledges that many domestic workers can be credited with harmoniously running the home, fulfilling elements of the role of the employer, and ensuring the employer’s children are cared for and supervised. Muslim female employers in particular teach and entrust their domestic workers to clean their home in line with Islamic principles and, more importantly, ensure their children are cared for and guided towards an Islamic path when left under the supervision of the domestic worker. The role of the mother in the home is emphasised in Islam, and thus, her helper must be an extension of that role, be it dusting with a ‘paak’ (clean) cloth or ‘deening’ (practicing tenets of an Islamic lifestyle). Building on previous qualitative research, this paper argues that domestic workers in South African Muslim homes must not only be ‘good’ cleaners – they must also understand, absorb, and display elements of Islam, both as cleaners and carers, in order to successfully fulfil their role as a trusted part of the Muslim home in South Africa. This paper also explores gendered bonds shared between employers and domestic workers, as mothers and wives, and how religion and remuneration influence this dynamic.